Research into Transformations in Everyday Life: Three Methodological Notes - Kubátová, Helena (Qualitative Sociology Review, 2018)
The article focuses on the reflection of my research experience in obtaining qualitative data using narrative interviews. I confronted my own research experience with the phenomenological methodology of Alfred Schütz, dramaturgical sociology of Erving Goffman, and interpretative sociology of Max Weber. The article discusses three problems that emerged during a longitudinal study of everyday life transformation in the long-term horizon of sixty years: 1. How to create a concept of everyday life so it serves not only as a tool for collecting, analyzing, and interpreting data, but also as a tool for understanding the meanings of the examined empirical world; 2. How to discursively create an image of everyday life transformations during an interview between a participant and a researcher and what it means in relation to the research subject; 3. How to reach understanding between the participant and the researcher during a face-to-face interview.